Iron deficiency anemia despite effective gluten-free diet in celiac disease: Diagnostic role of small bowel capsule endoscopy. Issue 4 (April 2017) - Efthymakis, Konstantinos; Milano, Angelo; Laterza, Francesco; Serio, Mariaelena; Neri, Matteo
Abstract: Background & aim: Iron deficiency anemia (IDA) is associated with celiac disease (CD). Although gluten-free diet (GFD) is an efficient treatment for CD, IDA remains an occasional finding during follow-up and correlates to inadequate gluten exclusion. Little is known regarding persistent IDA despite effective GFD. We aimed to evaluate the role of small bowel capsule endoscopy (SBCE) in this setting. Methods: We prospectively included consecutive patients undergoing GFD for ≥24 months with persistent concomitant IDA. Patients were assessed serologically and, if negative, underwent endoscopic evaluation. Results: Twenty-six patients underwent esophago-gastro-duodenoscopy (EGD), colonoscopy and SBCE. Altogether, 11 patients resulted positive. EGD showed mucosal lesions in 7: erosive gastritis (n = 3), erosive duodenitis (n = 1), active CD (n = 3). Colonoscopy showed hemorrhoids in 2. SBCE was positive in 6 cases: erosive jejunitis (n = 3, 1 eventually diagnosed as refractory CD, 2 as Crohn's disease), angiodysplasias (n = 2), lymphangectasia (n = 1). Some overlap was observed between procedures, since in 4 subjects EGD and SBCE produced significant findings. However, in 3 cases SBCE documented severe disease, not found at EGD. Hypoalbuminemia was significantly associated with a positive SBCE outcome ( p < 0.01). Conclusion: SBCE yielded significant findings in 23% of celiacs with persistent IDA despite adequate GFD. These were associated to hypoalbuminemia, indicating their occurrence at more severe stages of the disease.